Preclinical Pharmacology of CW002: A Nondepolarizing Neuromuscular Blocking Drug of Intermediate Duration, Degraded and Antagonized by l-cysteine—Additional Studies of Safety and Efficacy in the Anesthetized Rhesus Monkey and Cat. (October 2016) - Sunaga, Hiroshi; Savarese, John J.; McGilvra, Jeff D.; Heerdt, Paul M.; Belmont, Matthew R.; Van Ornum, Scott G.; Murrell, Matthew T.; Malhotra, Jaideep K.; Savard, Peter M.; Jeannotte, Erin; Petty, Bryce J.; Allen, Erica; et al.
Abstract : Background: CW002, a novel nondepolarizing neuromuscular blocking agent of intermediate duration, is degraded in vitro by L-cysteine; CW002-induced neuromuscular blockade (NMB) is antagonized in vivo by exogenous L-cysteine.1 Further, Institutional Animal Care and Use Committee–approved studies of safety and efficacy in eight anesthetized monkeys and six cats are described. Methods: Mean arterial pressure, heart rate, twitch, and train-of-four were recorded; estimated dose producing 95% twitch inhibition (ED95 ) for NMB and twitch recovery intervals from 5 to 95% of baseline were derived. Antagonism of 99 to 100% block in monkeys by L-cysteine (50 mg/kg) was tested after bolus doses of approximately 3.75 to 20 × ED95 and after infusions. Vagal and sympathetic autonomic responses were recorded in cats. Dose ratios for [circulatory (ED20 ) or autonomic (ED50 ) changes/ED95 (NMB)] were calculated. Results: ED95 s of CW002 in monkeys and cats were 0.040 and 0.035 mg/kg; L-cysteine readily antagonized block in monkeys: 5 to 95% twitch recovery intervals were shortened to 1.8 to 3.6 min after 3.75 to 10 × ED95 or infusions versus 11.5 to 13.5 min during spontaneous recovery. ED for 20% decrease of mean arterial pressure (n = 27) was 1.06 mg/kg in monkeys; ED for 20% increase of HR (n = 27) was 2.16 mg/kg. ED50 s for vagal and sympathetic inhibition in cats were 0.59 and >>0.80 mg/kg (n = 14 and 15). Dose ratios for [circulatory or autonomic changes/ED95 (NMB)] were all more than 15 × ED95 . Conclusions: The data further verify the neuromuscular blocking properties of CW002, including rapid reversal by L-cysteine of 100% NMB under several circumstances. A notable lack of autonomic or circulatory effects provided added proof of safety and efficacy. Abstract : L-cysteine caused rapid recovery of twitch from 5 to 95% of baseline within 1.8 to 3.6 min when it was administered to monkeys 1 min after doses of CW002 ranging from approximately 3.75 to 10 times the dose producing 95% twitch suppression (ED95 ; 0.15 to 0.40 mg/kg). The ratios of the doses producing a 20% decrease of mean arterial pressure or a 20% increase in heart rate in monkeys to the ED95 for neuromuscular blockade were 27 × ED95 and 54 × ED95, respectively.